Peritoneopericardial hernia associated with umbilical hernia and persistent urachus in a 7-months-old dog (Research, Society and Development, 2022)
Peritoneopericardial hernias (HDPP) are anatomic anomalies of the development of the diaphragm and pericardium that may be associated with other congenital alterations concomitantly. The aim of this report was to describe a case of peritoneopericardial hernia associated with umbilical hernia and persistent urachus treated in Pelotas/RS, furthermore to reviewing the clinical aspects, means of diagnosis and treatment on the subject, since it is a rare case. A dog, male, mixed breed dog, with seven months old, weighing 22kg was admitted at the Hospital de Clínicas Veterinárias, Universidade Federal de Pelotas, due to recurrent dyspnea and swelling in the umbilical region. Through chest X-ray and echocardiogram, HDPP was diagnosed. The patient was submitted to a preumbilical celiotomy and herniorrhaphy to correct the conditions. The same did not present complications during the post-surgical period. The study of cases like the one described above is very important for a better mapping of predispositions and associated conditions in congenital disorders, since they can lead to acute and/or chronic complications, putting the lives of dogs and cats at risk.